PENGARUH GOOD GOVERNANCE DAN PENGELOLAAN DANA TERHADAP KEPERCAYAAN PUBLIK KOTA SURABAYA - Taulo, Darren Nataleano Metusalak; Joko Priyono (widya balina, 2025)
Abstract. This study aims to determine the effect of Good Governance and Fund Management on Public Trust in the City of Surabaya, especially in the Kemayoran Village community. This study uses a quantitative method with an explanatory approach, where data are obtained through distributing questionnaires to 100 respondents who have interacted with public services. Data analysis was conducted using multiple linear regression with the help of SPSS software. The results of the study indicate that Good Governance and Fund Management simultaneously have a significant effect on Public Trust, as evidenced by the results of the F test with a significance value of <0.05. Partially, the Fund Management variable has a positive and significant effect on Public Trust, while the Good Governance variable has a positive but insignificant effect. The coefficient of determination (R²) value of 0.658 indicates that 65.8% of the variation in Public Trust is explained by these two variables. This finding indicates that transparency and accountability in public budget management are dominant factors in increasing public trust, while the implementation of Good Governance principles has not been fully perceived as effective by the public. Thus, optimizing the quality of fund management is an important strategy to strengthen government legitimacy in the eyes of the public.